Estudo dos compostos voláteis da decomposição térmica dos anti-helmínticos Albendazol e Mebendazol - Spazzini, Fabíola Cristina Ricci [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The albendazole and mebendazole drugs are benzimidazole derivatives and belong to the anthelmintic class. These drugs are particularly recommended for the treatment against worms present in the gastrointestinal tract of animals and humans, by acting directly on the worm metabolism. The need for thermally study drugs is related to all the parameters that these analyzes include: presence or absence of polymorphs, possible changes in the crystallinity of the drugs, as well as the quality control during the manufacturing process thereof. In this study the thermal behavior of anthelmintic albendazole and commercial mebendazole and its recrystallisation in organic solvents, such as acetic acid and formic acid in dimethylformamide to mebendazole, and albendazole were studied using TG-DSC techniques, TG-FTIR, FTIR and XRD. TG-DSC techniques were used so it could collect information about the thermal stability of the compounds steps for thermal decomposition process and also prove its melting temperature. For recrystallization of drugs in organic solvents, the TG-DSC curves were analyzed to compare and determine that the occurrence of polymorphs. The coupled TG-FTIR technique allowed the analysis of volatile products which were released during the thermal decomposition of the commercial mebendazole. The absorption spectroscopy in the infrared region was performed to mebendazole, and albendazole in order to show the difference in functional groups of both, comparing the spectra with commercial drugs and see if there was recrystallized changes in the absorption band where the drug was recrystallized or when heated. The diffraction technique by powder X-ray method was used for comparison of the crystal structures of commercial drugs and recrystallization in organic solvents to identify changes in crystallinity both, which might suggest the formation of polymorphs

Os fármacos albendazol e mebendazol são derivados do benzimidazol e pertencem à classe dos anti-helmínticos. Esses fármacos são recomendados principalmente para o tratamento contra vermes presentes no trato gastrointestinal de animais e humanos, agindo diretamente no metabolismo do verme. A necessidade de estudar termicamente os fármacos está relacionada a todos os parâmetros que essas análises incluem: existência ou ausência de polimorfos, possíveis mudanças na cristalinidade dos fármacos, bem como o controle de qualidade durante o processo de fabricação dos mesmos. Neste trabalho o comportamento térmico dos anti-helmínticos albendazol e mebendazol comerciais e de suas recristalizações em solventes orgânicos, tais como o ácido acético e ácido fórmico para o mebendazol e dimetilformamida para o albendazol foram estudados usando as técnicas de TG-DSC, TG-FTIR, FTIR e DRX. As técnicas TG-DSC foram utilizadas para que pudesse coletar informações sobre a estabilidade térmica dos compostos, etapas referentes ao processo de decomposição térmica e também comprovar sua temperatura de fusão. Para as recristalizações dos fármacos em solventes orgânicos, as curvas TG-DSC foram analisadas para que se comparasse e determinasse a ocorrência ou não de polimorfos. A técnica acoplada TG-FTIR permitiu a análise dos produtos voláteis que foram liberados durante o processo de decomposição térmica do mebendazol comercial. A espectroscopia de absorção na região do Infravermelho foi realizada para o albendazol e mebendazol a fim de mostrar a diferença dos grupos funcionais de ambos, comparar os espectros dos fármacos comerciais com o recristalizado e observar se houve alterações na banda de absorção quando o fármaco foi recristalizado ou quando foi aquecido. A técnica de difratometria de raios X pelo método do pó foi utilizada para a comparação das estruturas cristalinas dos fármacos comerciais e das...
Keywords: Espectroscopia de infravermelho; Abordagem interdisciplinar do conhecimento; Quimica; Pesquisa quimica; Anti-helminticos; Analise termica; Infrared spectroscopy